THE USE OF INTERNATIONAL AGREEMENTS LINKED TO THE EXPORT SIGNED BY THE PROVINCE OF SALTA BETWEEN 2003 AND 2015 BY SALTA’S PRODUCERS OF THE AGRICULTURAL SECTOR (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
The purpose of this article is to present in a succinct way the results of the research carried out within the framework of the Master's thesis in Business Administration. Specifically, the objective of the research consisted of investigating the knowledge of Salta agricultural producers about the international agreements related to export, signed by the Province of Salta between 2003 and 2015 and what use they made of them. From there, the investigation analyzed the impact that these agreements had on exports from the province. In order to reach this point, it was necessary to describe the institutional and economic legal framework in which said agreements were celebrated and to study them in light of the theories of international negotiation. Methodologically document analysis by categories was used, as well as interviews and statistical analysis, as an empirical support of the statements made in the work. The results obtained also allowed to identify the profile of the international management of the province in the period of time delimited by the investigation. The conclusions reached indicate that the knowledge of these instruments is scarce and that the broad nature that they usually have, make their operation diffucult, so it is necessary that they be accompanied by actions and concrete measures related to the exportable supply of the province.
Keywords: International Agreements; Exports; International Negotiations; International Management